Intracellular catalysis of disulfide bond formation by the human sulfhydryl oxidase, QSOX1 - Chakravarthi, Seema (Portland Press Ltd., 2007)
The discovery that the flavoprotein oxidase, Erv2p, provides oxidizing potential for disulfide bond formation in yeast, has led to investigations into the roles of the mammalian homologues of this protein. Mammalian homologues of Erv2p include QSOX (sulfhydryl oxidases) from human lung fibroblasts, guinea-pig endometrial cells and rat seminal vesicles. In the present study we show that, when expressed in mammalian cells, the longer version of human QSOX1 protein (hQSOX1a) is a transmembrane protein localized primarily to the Golgi apparatus. We also present the first evidence showing that hQSOX1a can act in vivo as an oxidase. Overexpression of hQSOX1a suppresses the lethality of a complete deletion of ERO1 (endoplasmic reticulum oxidase 1) in yeast and restores disulfide bond formation, as assayed by the folding of the secretory protein carboxypeptidase Y.